2022
DOI: 10.1001/jamanetworkopen.2022.16642
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Age, Sex, Lack of Response to Intravenous Immunoglobulin, and Development of Coronary Artery Abnormalities in Children With Kawasaki Disease in Japan

Abstract: Key Points Question Are age and sex associated with unresponsiveness to intravenous immunoglobulin (IVIG) and the development of coronary artery abnormalities (CAAs) among patients with Kawasaki disease (KD)? Findings This cohort study using data from 2414 patients in Japan identified an association between the proportion of patients with initial unresponsiveness to IVIG and increasing age. Differences in the risk factors were observed between initial unres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Subsequent multivariable analysis identified age <1 year and pre‐ Z ‐max as independent risk factors for CAAs. The finding that age <1 year is a risk factor for CAA is consistent with previous studies 23–25 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subsequent multivariable analysis identified age <1 year and pre‐ Z ‐max as independent risk factors for CAAs. The finding that age <1 year is a risk factor for CAA is consistent with previous studies 23–25 …”
Section: Discussionsupporting
confidence: 92%
“…The finding that age <1 year is a risk factor for CAA is consistent with previous studies. [23][24][25] Autopsy examinations have shown that changes in the coronary artery wall begin with inflammatory cell infiltration on the sixth to eighth days, whereas dilation begins from the 12th day. 26 Dilation of the coronary artery wall can likely occur earlier than the sixth to eighth days.…”
Section: Discussionmentioning
confidence: 99%
“…IVIG is the first-line treatment of KD with well-established therapeutic effects in preventing coronary artery abnormalities [ 41 ]. However, the criteria for when to provide IVIG are unclear and differ from the latest guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the incidence of CAA was significantly different between sub-groups according to age and sex in selected patients when using the different scoring systems, which lends further support to the results of Kitano et al [ 38 ]. The different triggers, weak immune response, and immature coronary arteries of infants may contribute to the vulnerability to CAA formation in infants with KD even if they respond to initial IVIG treatment [ 40 ]; however, the real reason remains a mystery. Furthermore, a prospective study on 3,043 people aged 18–30 years revealed that the prevalence of coronary artery calcium was significantly higher in men than in women (15% vs. 5.1%) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%